The Forgotten Educator: Experiential Learning's Internship Supervisor. Issue 1 (2nd January 2017) - Sosland, Jeffrey K.; Lowenthal, Diane J.
ABSTRACT: Past studies have addressed the role of the university, student interns and, the faculty advisor; here, we attempt to fill in a missing piece of the experiential-learning process by examining the role and importance of the often overlooked internship supervisor. A survey was developed and distributed to 343 recent internship supervisors. Their responses show that many of these supervisors view internships as an important professional and educational experience. We argue here that the internship supervisor can maximize one's effectiveness when operating within a strong college or university educational infrastructure facilitated by an engaged and competent faculty advisor. Our recommendations were discussed and confirmed by a focus group of experienced faculty advisors.